A Multiple Linear Regression Approach for the Analysis of Stress Factors of Faculty in Higher Educational Institutions - P. Ramesh Reddy; K. L. A. P. Sarma (International Journal of Mathematics And its Applications, 2015)
One of the fast growing sectors in India and abroad is an education sector. This sector masses highly qualified and committed faculty to enhance the quality of education and also to equip the student to meet demand of the industry. In this process faculty has to face many challenges and difficulties to meet the requirements of the education sector. The objective of the present study is under taken to address the effects of different inducing stress factors on job stress of the faculty in higher educational institutions of chittoor district, Andhra Pradesh. Instrument was used in order to get the responses from higher education institutions faculty to achieve the above stated objective. Multiple linear regression and ANOVA were used to analyze the data collected from 500 respondents. Different models were suggested to different categories of faculty members in higher educational institutions to measure their occupational stress and also identified highly contributed factors related to job stress to prevent professional burnout of faculty in higher education.